Effect of microchannel wall dimensions and temperature on ethylene glycol fluid's thermal performance in two-dimensional microchannels using molecular dynamics simulation - Li, Linxiang; Bagheri, Hadi; Sajadi, S. Mohammad; Yang, Chunsheng; Andriukaitis, Darius; Li, Z.; İnç, Mustafa (Elsevier Sci Ltd, 2023)
Increasing the transfer(HT) coefficient used in thermal industries is very important. Various methods are used to improve the efficiency of thermal heat HT so that maximum HT takes place in a smaller space. Ethylene glycol (EG) is generally used as an agent for convective HT. EG obtains energy from a hot source and discharges it to the required location. At present, the most consumption of EG is to produce engine cooling fluid. In the upcoming research, the TB of EG fluid in two-dimensional microchannels(MCs) has been investigated using molecular dynamics (MD) simulations, and the effect of variables such as MC dimensions and MC wall temperature(Temp) on the TB of the simulated fluid has been investigated. The results revealed that by increasing the Temp dif-ference of the MC wall from 10 to 50 K, the maximum temperature (Max-Temp) and velocity (Max-Vel) of the target sample increased to 640.94 K and 0.024 angstrom/ps. It can be concluded that the increase in the cross-sectional area and the wall Temp difference leads to an increase in the HT rate in the MC.
Keywords: Engine cooling; Thermal behavior; Ethylene glycol; MC; Molecular dynamics simulation